Motion Model and Speed Control of the Cross-Stream Active Mooring System for Tracking Short-Term Meandering to Maximize Ocean Current Power Generation. (April 2019) - Tsao, C. C.; Feng, A. H.
ABSTRACT: This paper analyzes the speed of lateral movement of the Cross-stream Active Mooring (CSAM) system in an ocean current and its control methods in order to study the system's capability of tracking short term meandering of ocean currents for maximizing power generation capacity. The CSAM concept for marine current power features a hydro sail system that can deploy generator turbines transversely across streams in a marine current. The hydro sail system can further adjust the horizontal position of the turbines, by changing the angle of attack of the hydro sail, to actively track fast streams in the marine current to increase power generation capacity. A two-step motion model with analytical formulas was developed and analysis based on mechanics indicated that the simplified model is adequate to estimate the system speed. Using an example system, it was estimated that the proposed active mooring system is capable of matching typical lateral speed of short term meandering and tracking fast streams in an ocean current without any external propulsion other than controlling the angle of attack of the hydro sails. Methods of controlling the system speed of moving from one location to another were also developed.